1990
DOI: 10.1093/oxfordjournals.aje.a115485
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors and Impaired Glucose Tolerance: The San Luis Valley Diabetes Study

Abstract: Cardiovascular risk factor patterns were examined cross-sectionally in 856 Hispanic and Anglo subjects aged 20-74 years enrolled in the population-based San Luis Valley Diabetes Study of Colorado. Risk factor levels and prevalence were compared for 279 individuals with non-insulin-dependent diabetes mellitus, 89 with impaired glucose tolerance, and 488 with normal glucose tolerance. Sex-specific comparisons of continuous risk factors were made by diabetic status and ethnicity, adjusting for age using two-way a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 0 publications
2
35
0
1
Order By: Relevance
“…Burchfiel et al [7] found that subjects with IGT had increased cardiovascular risk factors (decreased high density lipoprotein (HDL) cholesterol and increased triglyceride, blood pressure, and plasma insulin) intermediate between subjects with NGT and NIDDM. In a study of elderly subjects, Mykkä nen et al [8] found that men and women with IGT had significantly higher total triglycerides, apolipoprotein B (apo B) and lower HDL cholesterol and apo A than men and women with NGT.…”
Section: Igt and Cardiovascular Factorsmentioning
confidence: 99%
“…Burchfiel et al [7] found that subjects with IGT had increased cardiovascular risk factors (decreased high density lipoprotein (HDL) cholesterol and increased triglyceride, blood pressure, and plasma insulin) intermediate between subjects with NGT and NIDDM. In a study of elderly subjects, Mykkä nen et al [8] found that men and women with IGT had significantly higher total triglycerides, apolipoprotein B (apo B) and lower HDL cholesterol and apo A than men and women with NGT.…”
Section: Igt and Cardiovascular Factorsmentioning
confidence: 99%
“…Subjects with impaired glucose tolerance (IGT) are at an increased risk of developing diabetes and cardiovascular disease (6)(7)(8)(9). However, diagnosis of IGT requires an oral glucose tolerance test (OGTT), the use of which was abandoned by the ADA.…”
mentioning
confidence: 99%
“…However, few of these previous studies have been conducted in a sample representative of the general U.S. population (4,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)20). Moreover, it is unclear whether this excess mortality is conferred by PCH per se or rather by fasting hyperglycemia or CVD risk factors that commonly accompany diabetes, such as high blood pressure, dyslipidemia, and obesity (1,(21)(22)(23)(24)(25). Although there is mounting evidence of the importance of PCH, the prognostic value of this measure in the general U.S. population, especially as it relates to mortality, remains unclear.…”
mentioning
confidence: 99%